2016
DOI: 10.1016/j.triboint.2016.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, thermal and tribological properties of polyimide/nano-SiO2 composites synthesized using an in-situ polymerization

Abstract: Polyimide (PI)/nano-SiO 2 composites were successfully fabricated via a novel in-situ polymerization. Microstructure, thermal properties, mechanical performance and tribological behaviors of these composites were investigated. The results indicate that nano-SiO 2 dispersed homogeneously. Compared with pure PI, thermal stability and heat resistance are higher about 10℃ with the addition of 5 wt% nano-SiO 2. Compressive strength and modulus of composite with 5 wt% nano-SiO 2 increase by 42.6 and 45.2%, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…PI was synthesized using tetracarboxydiphthalic ether dianhydride (ODPA) and 4,4′-diaminodiphenyl ether (ODA) as monomers via chemical imidization [1,22]. MPS was synthesized using tetraethoxysilane (TEOS) as the silica source along with octylamine (OA) as template in weak acid deionized water [1].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PI was synthesized using tetracarboxydiphthalic ether dianhydride (ODPA) and 4,4′-diaminodiphenyl ether (ODA) as monomers via chemical imidization [1,22]. MPS was synthesized using tetraethoxysilane (TEOS) as the silica source along with octylamine (OA) as template in weak acid deionized water [1].…”
Section: Methodsmentioning
confidence: 99%
“…Samyn et al [18][19][20] worked on tribochemical variations of PI and PI composites at room and elevated temperatures to understand the relationship between associated tribochemical variations and tribological properties of PI composites. In-situ polymerization method was employed initially to enhance tribological properties of PI composites, but with contrary outcomes obtained, possibly induced by combined effects of approaches, reinforcing agents and interfacial design [21,22]. Many reinforcing mechanisms [2,[6][7][8][9][10][11][12][13] were proposed to explain the reason for enhancing tribological properties of PI composites, consisting of the formation of high-quality triofilms, lubricity and preferential load bearing of fillers, as well as enhanced mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is confirmed that the presence of alkyl pendent groups in the polyimides cause the deterioration of thermal properties but bulky or long aryl side chains can retain those good heat resistant properties . As the percentage of nanofiller increases decomposition temperature increases because of the high thermal stability imparted by the silica which also acts as the heat sink absorbing heat there by inhibiting the decomposition .…”
Section: Resultsmentioning
confidence: 92%
“…It is well‐known that thermal and tribological properties of PI can be altered significantly by incorporating rigid nanoparticles and pores into PI resin . For instance, the inclusion of SiO 2 nanoparticles into PI resin was shown to increase the thermal stability of PI powders by 42°C . Nonetheless, when pores exist in PI resin, its thermal stability declines by 40–100°C instead .…”
Section: Introductionmentioning
confidence: 99%